PENGARUH MINAT DAN PEMBELAJARAN DARING TERHADAP TINGKAT PEMAHAMAN MATA KULIAH PENGANTAR AKUNTANSI (STUDI PADA MAHASISWA PERGURUAN TINGGI DI KOTA MALANG) - Suci Rachmadan; Noor Shodiq Askandar; Junaidi Junaidi (Universitas Islam Malang, 2021)
This study focuses on testing a theory by determining research variables regarding whether there is an influence between interest and online learning on the level of understanding of introductory accounting courses. This research data collection was carried out by distributing questionnaires through Google Form to research respondents. Data analysis using SPSS computer program. The result of this research is that interest and online learning have a significant effect on the level of understanding of introductory accounting courses for accounting students at the Islamic University of Malang, University of Muhammadiyah Malang, State University of Malang and State Islamic University of Maulana Malik Ibrahim Malang.Keywords: interest, online learning, course understanding level, and introduction of accounting.